A novel Ku‐band waveguide piezo‐electric air gap capacitor using a single tuning element - Loutridis, Abraham; Vagias, Ioannis; Leighton, Glenn J. T.; Shaw, Christopher P. (Institution of Engineering and Technology (IET), 2025)
In this work, a tuning element with controllable air gap integrated and implemented in a rectangular Ku‐band WR62 waveguide is presented. The proposed tuning element concept, consists of two, top and bottom, thin conductive parallelepiped arms, which are placed in the middle of the rectangular waveguide structure. The bottom arm is bending to control the gap width (w) between the two arms, whereas the second arm is fixed. The curvature of the bending arm is controlled by a piezo‐electric actuator, which affects the phase shift of the re‐scattered E‐field at the output port. The tuning element was designed with a 5% bandwidth centred at 15 GHz. The compact size, low‐cost and the easy‐to‐manufacture proposed design offers a considerable phase shift with very low insertion loss, given its electrical size and operational waveband. A prototype, for the distinct frequency band, has been manufactured and measured. The same prototype has been simulated in ANSYS HFSS. The numerical results will be later used to validate the actual electromechanical prototype.
Keywords: 40 Engineering; 4009 Electronics, Sensors and Digital Hardware; Networking & Telecommunications; 4006 Communications engineering; 4008 Electrical engineering